Measurement of higher-order harmonic azimuthal anisotropy in PbPb collisions at root s(NN)=2.76 TeV - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Eroe, J; Fabjan, C; Friedl, M; Fruehwirth, R; Ghete, V; et al. (2014)
Measurements are presented by the CMS Collaboration at the Large Hadron Collider (LHC) of the higher-order harmonic coefficients that describe the azimuthal anisotropy of charged particles emitted in sNN=2.76 TeV PbPb collisions. Expressed in terms of the Fourier components of the azimuthal distribution, the n=3-6 harmonic coefficients are presented for charged particles as a function of their transverse momentum (0.3